The Use of Smiling Clock As Learning Media In Teaching Telling Time For 5th Grade Students of Elementary School - Rika Septiani; Astri Julyawati (Jurnal Fakultas Keguruan & Ilmu Pendidikan Kuningan, 2023)
In the student learning process, learning media has a very important role. Seeing the low motivation of students towards learning Telling Time, is an indicator that understanding of the material is also low. Therefore, this study aims to determine the use of Smiling Clock learning media to support students’ success in learning Telling Time and to determine students’ perceptions of Telling Time learning using Smiling Clock media. This research was conducted at SDIT Al – Huda Kertawangunan by using qualitative descriptive data analysis techniques and data collection using observation, interviews, and documentation. The conclusion of this study is that the Smiling Clock learning media is one of the media that can support students’ success in learning Telling Time because by using the Smiling Clock media, 5th grade students of SDIT Al – Huda Kertawangunan can learn Telling Time material very good and the students strongly agree that Smiling Clock media is a unique and fun media so that Telling Time material is easier to understand.